Bicontinuous nanoporous design induced homogenization of strain localization in metallic glasses. (February 2021) - Liu, Chang; Yuan, Suyue; Branicio, Paulo S.
Abstract: Bicontinuous nanoporous metallic glasses (MG) synergize the outstanding properties of MGs and open-cell nanoporous materials. The low-density and high-specific-surface-area of bicontinuous nanoporous structures have the potential to enhance the applicability of MGs in catalysis, sensors, and lightweight structural designs. Here, we report molecular dynamics simulations of tensile loading deformation and failure of bicontinuous nanoporous Cu64 Zr36 MG with 55% porosity and 4.4 nm ligament size. Results indicate an anomalous mechanical behavior featuring delocalized plastic deformation preceding ductile failure. The deformation follows two mechanisms: i) Necking of ligaments aligned with the loading direction and ii) progressive alignment of randomly oriented ligaments. Failure occurs at 0.16 strain, following massive rupture of ligaments. This work indicates that a bicontinuous nanoporous design is able to effectively delocalize strain localization in a MG due to a combination of size effect on the ductility of MGs resulting in nano ligaments necking and progressive asynchronous alignment of ligaments. Graphical abstract: Image, graphical abstract